أداء الإطارات البيتونية المملوءة بجدران البلوك والحاوية على فتحات والمدعمة بشرائح الألياف الكربونية (CFRP)تحت تأثير الحمولات الجانبية في مستويها (Tishreen University, 2019)
Masonry walls are used as internal walls for architectural purposes . The effect of these walls is not considered during design or restoration, but only the architectural function is taken into account and the self weight are considered. This is due to the inability to determine the properties of resistance of these walls, and also because of the weak of resistance to tensile, but after the consideration of the impact of carbon fiber strips led to increase the ductility of these walls and change behavior and behavior collapse from the brittle to ductility collapse. Since these walls are the largest case of their presence in our reality is to contain openings, and because of the availability of carbon fiber strips from increasing the ductility of these walls, Where we studied the case of a RC frame surrounded by a wall of concrete block and containing doors and windows supported by carbon fiber strips, and adopted different ratios of these openings to dimensions of the wall, 7%,22%,34%for doors case and 7%, 22%,34%, 40% for windows case . Different positions were also adopted for these openings, namely the case of the terminal and middle opening.  We found that the Strengthening of these walls had a positive effect on the behavior of the frame and led to a large increasing of strength and ductility also for a case without a Strengthening. تستخدم جدران البلوك في الأبنية كقواطع من أجل الأغراض المعمارية ومن أجل لوازم القاطنين، حيث تشكل هذه الجدران إما قواطع داخلية أو خارجية، ولا يتم إدخال تأثير هذه الجدران أثناء التصميم أو إعادة الترميم وإنما تؤخذ فقط الوظيفة المعمارية لها واعتبار احمالها. ويعود ذلك إلى عدم القدرة على تحديد خواص مقاومة هذه الجدران، وأيضاً بسبب ضعف مقاومتها على الشد لكن إدخال تأثير شرائح الألياف الكربونية أدى إلى زيادة فعالية هذه الجدران وتغيير سلوكها وسلوك انهيارها من الحالة الهشة إلى الحالة المطاوعة. وبما أن الحالة الأكبر لتواجدها في واقعنا هي أن تحتوي على فتحات، ونظراً لما توفره شرائح الألياف الكربونية من رفع مطاوعة هذه الجدران، قمنا في ورقتنا البحثية هذه باعتماد تقوية جدران البلوك الحاوية على فتحات بشرائح الألياف الكربونية. حيث قمنا بدراسة حالة إطار بيتوني مسلح يحيط بجدار من البلوك الاسمنتي ويحتوي على فتحات أبواب ونوافذ ومدعم بشرائح الألياف الكربونية، وتم اعتماد نسب مختلفة لهذه الفتحات وذلك بالنسبة لأبعاد الجدار حيث اعتمدت النسب 7%,22%,34% من أجل حالة الأبواب، والنسب 7%, 22%,34%, 40% من أجل حالة النوافذ. كما تم اعتماد مواقع مختلفة لهذه الفتحات وهي حالة الفتحة الطرفية وحالة الفتحة الوسطية وتبين لنا أن تدعيم هذه الجدران أثر بشكل ايجابي على سلوك الإطار وأدى إلى رفع مطاوعته بشكل كبير ومقاومته أيضاً وذلك بالنسبة لحالة عدم وجود تدعيم.